2012
DOI: 10.1161/strokeaha.111.643932
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond a Single Perfusion Threshold to Define Penumbra

Abstract: Background and Purpose— The mismatch lesion volumes defined by perfusion-weighted imaging exceeding diffusion-weighted imaging have been used as a marker of ischemic penumbral tissue. Defining the perfusion lesion by thresholding has shown promise as a practical tool; several positron emission tomography studies have indicated a more probabilistic relationship between perfusion and infarction. Here, we used a randomized controlled trial dataset of tissue-type plasminogen activator 3 to 6 hours afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…A more probabilistic approach has demonstrated increasing infarction risk with increasing degrees of Tmax delay. 3 This appears to improve prediction of final infarct volume, although it cannot easily be applied to a spatial prediction. We hypothesize that increasing Tmax delay indicates tissue further down the collateral flow pathway with greater vulnerability to any reduction in collateral flow as a result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more probabilistic approach has demonstrated increasing infarction risk with increasing degrees of Tmax delay. 3 This appears to improve prediction of final infarct volume, although it cannot easily be applied to a spatial prediction. We hypothesize that increasing Tmax delay indicates tissue further down the collateral flow pathway with greater vulnerability to any reduction in collateral flow as a result.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, it is evident in clinical practice that infarct growth does not always progress to the full extent of the involved vascular territory, even in the absence of reperfusion. 3 This variability in outcome may well relate to the persistence or failure of collateral vessels over time.…”
Section: Introductionmentioning
confidence: 99%
“…Nagakane et al 29 showed that the risk of subsequent infarction increases if Tmax increases and that this probabilistic approach allowed a better prediction of the final infarction volume than single cutoff values. 29 It is likely that in patients with a longer collateral filling time there is an increased proportion of tissue-atrisk with higher Tmax values.…”
Section: Discussionmentioning
confidence: 99%
“…29 It is likely that in patients with a longer collateral filling time there is an increased proportion of tissue-atrisk with higher Tmax values. Assuming an increased likelihood of infarction for this tissue as suggested by Nagakane et al, this may explain the observed association between collateral filling time and infarct growth.…”
Section: Discussionmentioning
confidence: 99%
“…At admission, the median NIHSS score was 17 (IQR, [15][16][17][18][19][20]. Eleven patients had leftsided strokes with concomitant aphasic symptoms.…”
Section: Resultsmentioning
confidence: 99%